The Sacrilege of Feminism: Светогрдието на феминизмот - Cornell, Drucilla; Naumovska, Senka (Identities: Journal for Politics, Gender and Culture, 2002)
Author(s): Drucilla Cornell | Друсила Корнел Title (English): The Sacrilege of Feminism Title (Macedonian): Светогрдието на феминизмот Translated by (English to Macedonian): Senka Naumovska | Сенка Наумовска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 3 (Summer 2002) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 9-16 Page Count: 8 Citation (English): Drucilla Cornell, “The Sacrilege of Feminism,” Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 3 (Summer 2002): 9-16. Citation (Macedonian): Друсила Корнел, „Светогрдието на феминизмот“, превод од англиски Сенка Наумовска, Идентитети: списание за политика, род и култура, т. 1, бр. 3 (лето 2002): 9-16.